Multichannel detectors for femtosecond stimulated Raman microscopy – ideal and real ones1. (1st July 2014) - Marx, B.; Czerwinski, L.; Light, R.; Somekh, M.; Gilch, P.; Moger, Julian; Radi, Peter
<x xml:space="preserve">Abstract</x> Femtosecond stimulated Raman microscopy (FSRM) aims at the reduction of acquisition times in Raman microscopy while preserving the spectral coverage. An improved light source for FSRM is briefly described. This light source delivers a narrow bandwidth Raman pump pulse and a broad‐band Raman probe. The small spectral changes (relative magnitude 10−6 to 10−3) in the probe light due to the stimulated Raman effect are recorded simultaneously relying on array detectors. Here, estimates for the parameters of an ideal detector are derived and compared with the technical status quo of available detectors. Copyright © 2014 John Wiley & Sons, Ltd.